2011
DOI: 10.1007/s00395-011-0172-1
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated protein kinases activation in T lymphocytes of patients with acute coronary syndromes

Abstract: Current available biomarkers cannot identify myocardial ischemia without necrosis. To overcome this issue and to increase diagnostic power, we evaluated the activation of the three MAPK pathways, ERK1/2, JNK and p38, in T lymphocytes of patients with acute coronary syndromes (ACS). We included sixty consecutive patients affected by either unstable angina (UA, N = 22), Non- ST-segment elevation MI (NSTEMI, N = 19) or ST-segment elevation MI (STEMI, N = 19). Two separate groups of patients were matched as contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…MAPK1 belongs to the Ser-Thr kinases protein family and has been previously reported in different features of cardiac modeling and regulation of inflammation, cell proliferation and differentiation ( 55 , 56 ). The high activity of Erk1/2 has been observed in T-lymphocytes from CAD patients, including ST-elevation myocardial infarction (STEMI), Non-STEMI and unstable angina ( 57 ). A previous study demonstrated the EGFR-mediated cross-talk between MAPK and Akt1 signaling, which combined had an important role in abnormal vascular remodeling ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…MAPK1 belongs to the Ser-Thr kinases protein family and has been previously reported in different features of cardiac modeling and regulation of inflammation, cell proliferation and differentiation ( 55 , 56 ). The high activity of Erk1/2 has been observed in T-lymphocytes from CAD patients, including ST-elevation myocardial infarction (STEMI), Non-STEMI and unstable angina ( 57 ). A previous study demonstrated the EGFR-mediated cross-talk between MAPK and Akt1 signaling, which combined had an important role in abnormal vascular remodeling ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…The renin-angiotensin system has been classically shown to be a major regulator of pathologic cardiac hypertrophy [6]. Indeed, Angiotensin II (AngII) is rapidly released from myocardial cells in response to cardiac damage and stretch; after binding to the AT1R, through Src, Ras, Gq and PKC mediation, it activates the maladaptive extracellular signal-regulated protein kinase 1/2 (ERK1/2) generating pathological cellular growth [20,30,4649]. Valsartan, a classic non-competitive antagonist of the AT1R, has been widely used in the clinical setting for the treatment of patients with systemic hypertension and concentric cardiac hypertrophy [50].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is able to cause biochemical responses (25) and then trigger MAPK, which plays important roles through phosphorylating intracellular substrates, thereby mediating signal transduction, as well as specific genetic responses to extracellular stimuli (26). MAPK activation in UA to a complete MAPK activation in MI, has been proved effective as a diagnostic test to discern the difference between ACS conditions (27). Accordingly, MAPK is a valuable molecular biomarker serving as specific signature for the diagnosis of UA/MI.…”
Section: Discussionmentioning
confidence: 99%